Changes in the labor supply behavior of married women: 1980-2000 - Blau, Francine D.; Kahn, Lawrence M. (Bonn, 2006)
"In this paper, we investigate the effects of the boom in education on the wage structure in Europe. We use detailed information on the distribution of wages, estimated from microdata from 12 European countries from the beginning of the 1980’s to the present, to analyse the changes both between and within groups. We specify and estimate a model with supply and demand for different types of labour, as well as institutions affecting the bargained relative wage. Our results show that the boom in education closely matched the shifts in demand due to (skill biased) technological change, which in turn explains why the wage premia for education only rose moderately. We use the conditional wage spread within tertiary education, predicted from quantile log wage regressions, to investigate the hypothesis of skills erosion as a result of the large expansion in tertiary education. We find no evidence in favour of the hypothesis that the boom in higher education lead to an erosion of skills within the group of tertiary education, nor evidence of increasing “over-education” in Europe. Labour market institutions also matter: bargaining co-ordination and employment protection are shown to have a compressing effect on wages, but at different points of the wage distribution. "